2014 National Winter Canola Variety Trial - Stamm, Michael; Dooley, Scott J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2016)
The objectives of the National Winter Canola Variety Trial (NWCVT) are to evaluate the performance of released and experimental varieties, determine where these varieties are best adapted, and increase the visibility of winter canola across the United States. Breeders, marketers, and producers use data collected from the trials to make informed variety selections. The NWCVT is planted at locations in the Great Plains, Midwest, northern U.S., and Southeast. Senior Authors Michael Stamm, Dept. of Agronomy, Kansas State University, Manhattan Scott Dooley, Dept. of Agronomy, Kansas State University, Manhattan Other Contributors Sangu Angadi and Sultan Begna, New Mexico State University, Clovis Brian Baldwin, Mississippi State University, Starkville Abdel Berrada, Colorado State University, Yellow Jacket Harbans Bhardwaj, Virginia State University, Petersburg Indi Braden, Southeast Missouri State University, Cape Girardeau Joshua Bushong, Oklahoma State University, Stillwater Brian Caldbeck, Caldbeck Consulting, Philpot, Kentucky Claire Caldbeck, Rubisco Seeds, Philpot, Kentucky Ernst Cebert, Alabama A&M University, Normal Jeff Chandler, North Carolina State University, Mills River Gary Cramer, Kansas State University, Wichita John Damicone and Tyler Pierson, Oklahoma State University, Stillwater Heather Darby, University of Vermont, St. Albans Jeffery Davidson, Mike Bartolo, and Kevin Tanabe, Colorado State University, Rocky Ford Jim Davis and Megan Wingerson, University of Idaho, Moscow Dennis Delaney, Auburn University, Auburn, Alabama Paul DeLaune, Texas AgriLife Research Service, Vernon Eric Eriksmoen, North Dakota State University, Minot John Garner and Adam Heitman, North Carolina State University, Wallace John Gassett, Mitch Gilmer, H. Jordan, and Gary Ware, University of Georgia, Griffin Nicholas George, University of California-Davis Brent Gruenbacher and Mike Patry, Andale, Kansas Todd Higgins, Lincoln University, Jefferson City, Missouri Johnathon Holman, Kansas State University, Garden City Burton Johnson, North Dakota State University, Fargo Jerry Johnson, Colorado State University, Ft. Collins Rick Kochenower, Oklahoma State University, Goodwell Kevin Larson, Colorado State University, Walsh David Lee and Melvin Henninger, Rutgers University, Woodstown, New Jersey Charles Mansfield, Vincennes University, Vincennes Lloyd Murdock and John James, University of Kentucky, Lexington Jerry Nachtman, University of Wyoming, Lingle Clark Neely and Daniel Hathcoat, Texas A&M University, College Station Mick O’Neill and Curtis Owen, New Mexico State University, Farmington Calvin Pearson, Colorado State University, Fruita Charlie Rife, High Plains Crop Development, Torrington, Wyoming Dipak Santra, University of Nebraska-Lincoln, Scottsbluff Robert Schrock, Kiowa, Kansas Peter Sexton, South Dakota State University, Brookings Tyler Thomas, Fly Over States Ag Research, Troy, Kansas Wade Thomason and Steve Gulick, Virginia Tech University, Blacksburg Calvin Trostle and Jonathan Shockey, Texas AgriLife Extension Service, Lubbock Dennis West, University of Tennessee, Knoxville Amber Williams, USDA-ARS, Temple, Texas
Keywords: Canola; Kansas; Yield; Environmental factors; Oil